The Controversy of Prohibiting Marriage in the Month of Syawal in Minangkabau Traditions - Sari, Veni Mulya; Firdawaty, Linda; Mohd Said, Mohd Helmi; Deswita, Nurfia (El-Izdiwaj: Indonesian Journal of Civil and Islamic Family Law, 2023)
This research examines the controversy surrounding the prohibition of marriage in the month of Syawal among the Minangkabau community in Nagari Batupalano. Beliefs that encompass traditions from ancestors influence the personal mentality of the community. This study focuses on the perspectives of religious leaders (ulama), traditional leaders, and community figures. The research type is field research, descriptive in nature, and utilizes both primary and secondary data sources. Data collection involves observation, interviews, and documentation. The research findings indicate that the reasons stated by the Nagari Batupalano community for maintaining this tradition are twofold. Firstly, the tradition of prohibiting marriage in the month of Syawal is considered an ancestral heritage that has been agreed upon and recognized by the Nagari Batupalano community since ancient times until the present. Secondly, the reasons expressed aim to avoid misfortune caused by marrying in Syawal, as it is considered a month associated with bad luck (anyuki kasai). Engaging in marriage ceremonies, celebrations, and similar activities during this period is believed to lead to divorce. From an Islamic family law perspective, no specific prohibition related to this tradition is found in the Qur'an and Hadith. For those who still believe in the prohibition of marriage in the month of Syawal, this tradition falls under Al-'urf khâsh (specific tradition) and Urf fasid, and it is advisable not to believe in it as it may have the potential to lead to acts of shirk